An Approximation for Direct and Inverse Problems Related to Longitudinally Inhomogeneous Waveguides - (:unkn) unknown (IEEE, 2016)
An approximation is derived for longitudinally inhomogeneous waveguides (LIW). Total reflections are adopted for a rough approximation through the tracking of the main reflected and transmitted fields in the multilayered dielectric structure. This approximation can be used to determine the thickness of layers of which the dielectric properties are known. Although the obtained thickness values are a rough approximation for the exact values, they provide a utility for iterative optimization algorithms for which the initial values are vital.
Keywords: Longitudinally Inhomogeneous Waveguides; Direct and inverse problems; Generating initial values for iterative optimization methods; DIELECTRICS